Ascorbate synthesis as an alternative electron source for mitochondrial respiration: Possible implications for the plant performance - Matos, Isabelle Faria; Morales, Luis Miguel Mazorra; Santana, Diederson Bortolini; Silva, Gláucia Michelle Cosme; Gomes, Mara Menezes de Assis; Ayub, Ricardo Antônio; Costa, José Hélio; Oliveira, Jurandi Gonçalves de (Frontiers in Plant Science, 2022)
The molecule vitamin C, in the chemical form of ascorbic acid (AsA), is known to be essential for the metabolism of humans and animals. Humans do not produce AsA, so they depend on plants as a source of vitamin C for their food. The AsA synthesis pathway occurs partially in the cytosol, but the last oxidation step is physically linked to the respiratory chain of plant mitochondria. This oxidation step is catalyzed by L-galactono-1,4-lactone dehydrogenase (L-GalLDH). This enzyme is not considered a limiting step for AsA production; however, it presents a distinguishing characteristic: the L-GalLDH can introduce electrons directly into the respiratory chain through cytochrome c (Cytc) and therefore can be considered an extramitochondrial electron source that bypasses the phosphorylating Complex III. The use of Cytc as electron acceptor has been debated in terms of its need for AsA synthesis, but little has been said in relation to its impact on the functioning of the respiratory chain. This work seeks to offer a new view about the possible changes that result of the link between AsA synthesis and the mitochondrial respiration. We hypothesized that some physiological changes related to low AsA may be not only explained by the deficiency of this molecule but also by the changes in the respiratory function. We discussed some findings showing that respiratory mutants contained changes in AsA synthesis. Besides, recent works that also indicate that the excessive electron transport via L-GalLDH enzyme may affect other respiratory pathways. We proposed that Cytc reduction by L-GalLDH may be considered as alternative respiratory pathway that is active during AsA synthesis. Also, it is proposed that possible links of this pathway with other pathways of alternative electron transport in plant mitochondria may exist. The review suggests possible implications of this relationship, particularly for situations of stress. We hypothesized that the L-GalLDH may be part of a pathway of alternative electron transport that would serve as a strategy for adaptation of plant respiration to changing conditions.